A comprehensive method for the fracability evaluation of shale combined with brittleness and stress sensitivity. (25th October 2017) - Wang, Xiaoqiong; Ge, Hongkui; Wang, Daobing; Wang, Jianbo; Chen, Hao
Abstract: An effective fracability evaluation on the fracture network is key to the whole process of shale gas exploitation. At present, neither a standard criteria nor a generally accepted evaluation method exist. Well log and laboratory results have shown that the commonly used brittleness index calculated from the mineralogy composition is not entirely consistent with that obtained from the elastic modulus of the rock, and is sometimes even contradictory. The brittle mineral reflects the brittleness of the rock matrix, and the stress sensitivity of the wave velocity reflects the development degree of the natural fracture system. They are both key factors in controlling the propagating fracture morphology. Thus, in this study, a novel fracability evaluation method of shale was developed combining brittleness and stress sensitivity. Based on this method, the fracability of three shale gas plays were evaluated. The cored cylindrical samples were loaded under uniaxial stress up to 30 MPa and the compressional wave velocities were obtained along the axis stress direction at each MPa stress. From the stress velocity evolution, the stress sensitivity coefficients could be obtained. Our results showed that the fracability of Niutitang shale is better than that of Lujiaping shale, and the fracability of Lujiaping shale is better than Longmaxi shale. This result is in good agreement with acoustic emission activity measurements. The new fracability evaluation method enables a comprehensive reflection of the characteristics of rock matrix brittleness and the natural fracture system. This work is valuable for the evaluation of hydraulic fracturing effects in unconventional oil and gas reservoirs in the future.